Psychological well-being of personality - Aleshchenko, Viktor (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2024)
Background. The relevance of the study of the psychological well-being of an individual is due to the need to clarify the content, characteristics and criteria of this phenomenon, as well as to identify a functional model of the psychological well-being of an individual based on the theoretical analysis of the works of scientists and own research. The purpose of the article is to determine the essence, structure and factors of a person's psychological well-being. To find out the nature of the phenomenon of psychological well-being; describe the main criteria of psychological well-being; analyze the characteristics of psychological well-being.Methods. To achieve the goal, such scientific methods were used as: analysis, comparison, substantiation, generalization, systematization of theoretical and practical material on psychological well-being.Results. Considered examines the phenomenon of psychological well-being of an individual as an integrative formation, which manifests itself in the degree of focus on the fulfillment of the main components of positive human functioning, subjectively perceived as satisfaction withoneself and one's life. It has been established that the psychological well-being of an individual is related to his or her value orientations (life goals, life processes, and life efficiency) and vitality. It is shown that psychological well-being is the result of a sense of achievement and success inprofessional activities, harmony in personal life and attitude towards people.Сonclusions. Psychological well-being and its components help to understand the role of mental health (if we consider health as a component of well-being), its conditions and factors (if we consider a healthy personality) as a mature, authentic and successful self-actualized person in various areas. Psychological well-being is an indicator of a person's state of health, his social and psychological adaptability and efficiency of functioning.
Keywords: psychological well-being, internal resources, personality, personal potential, attitude towards people